FORMULASI DAN EVALUASI FISIK SEDIAAN EYESHADOW STICK DARI EKSTRAK KULIT BUAH TERONG BELANDA (Solanum betaceum Cav.) SEBAGAI PEWARNA ALAMI - Habibie Deswilyaz Ghiffari; Rastria Meilanda; Larasati Dinda Meditha (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2025)
The skin of the Dutch eggplant contains anthocyanin compounds that serve as colorants. The skin exhibits an attractive red color, making it a potential natural dye alternative in cosmetics. This study aims to formulate and evaluate the physical properties of an eyeshadow stick made from Dutch eggplant skin extract. An experimental research method was employed, creating four formulations of the eyeshadow stick by varying the concentration of the Dutch eggplant skin extract: F0 (0%), F1 (6%), F2 (12%), and F3 (24%). Physical evaluations of the eyeshadow stick were conducted weekly over four weeks at room temperature (25°C), assessing parameters such as organoleptic properties, homogeneity, spreadability, and melting point. Additionally, a cycling test was performed over six cycles for 12 days, along with irritation tests and preference tests involving 10 volunteers. The results indicated that the organoleptic properties of the three formulations resulted in light pink, medium pink, and dark pink colors, with a white base, a rose scent, and a semi-solid form. There was a significant difference (p < 0.05) in spreadability among F0, F1, F2, and F3, showing that as the extract concentration increased, spreadability decreased, falling within the range of 5-7 cm. All formulations remained stable during storage according to the cycling test results. The irritation tests revealed that none of the formulations caused redness, itching, or swelling. The best formulation was identified as F3 with a 24% extract concentration.